The Effect of Temperature Variation on Quality of Desiccated Coconut Dried in Desiccated Coconut Dryer - Wilson Lapiga Ginting; Lukman Adlin Harahap; Ainun Rohana (Universitas Sumatera Utara, 2015)
Drying of grated coconut is a food processing technology that can produce healthy food without much changing it’s original nature like taste, aroma, color and nutrient of the food. This research was aimed at testing the temperature drying on the quality of the desiccated coconut dried in desiccated coconut dryer. Therefore, a research had been conducted using a non- factorial completely randomized design with drying temperature of (100⁰C, 110⁰C, 120⁰C and 130⁰C). Parameters observed were moisture content, yield and organoleptic tests. The results showed that drying temperature had significant effect on water content, yield and color and had no significant effect on aroma and overall acceptance. The best results were obtained at a temperature of 130⁰C. Keywords: Desiccated Coconut, Dryer , Temperature